Exploring the impact of nucleic acids on protein stability in bacterial cell lysate - Ham, Soojeong; Lee, Changhan (Biochimica et Biophysica Acta - General Subjects, 2023)
- Addition of salt enhanced thermal stability of model substrate proteins by reducing electrostatic repulsion between protein molecules. - However, the opposite effect was observed with bacterial cell lysate, indicating that certain molecules within the lysate could enhance protein stability via electrostatic interactions. - Such molecules present in cell lysate were found to be nucleic acids known to have a potent anti-aggregation activity toward proteins involving electrostatic interactions. - Nucleic acids showed chaperone activity in physiological salt concentration within cells and in buffer or medium commonly used in experiments. - The chaperone activity of nucleic acids should be taken into account when performing various in vitro assays using cell lysate or samples containing nucleic acids.
Keywords: Nucleic Acids; Protein Folding; Protein Stability; Static Electricity; Anti-aggregation activity; Chaperone; DNA; Nucleic acids; RNA